Chapter Wealth inequality in Catalonia, 1400-1800. Sources, data and a case study - GARCIA MONTERO, HECTOR (Datini Studies in Economic History, 2020)
This work is part of the research carried out within the EINITE and SMITE projects for the case of Catalonia. In this chapter, firstly, a brief state of the art of research carried out in recent years on the evolution of economic inequality in the pre-industrial world is traced. Subsequently, through the previously existing literature and the study of the empirical evidence compiled for this work, the characteristics of the fiscal sources available for some Catalan localities, i.e. the books of estimes, vàlues or manifests, and the sample of localities studied in the EINITE/SMITE projects are described in detail. The second part of the work focuses on the analysis of a case study, the town of Balaguer.